Produtividade e avaliação nutricional do girassol adubado com lodo de esgoto - Hermann Cruz de Albuquerque (2012)
Sewage sludge is rich in organic matter and nutrients, and has great potential for use in fertilization of oilseeds. This study aimed to evaluate the effect of applying sewage sludge heat-dry on soil fertility, growth and productivity of sunflower (Helianthus annuus L.). The experiment was carried out in Red-Yellow Latosol at Institute of Agricultural Sciences (ICA/UFMG) in Montes Claros-MG. The treatments consisted of 4 doses of sewage sludge (0; 10; 20 and 30 t ha-1, dry basis), with six replications, in randomized design. Evaluations were made of the nutrient levels in the soil and in the plant, the indexes of soil fertility, the stem diameter, the height plant, the head diameter and the yield. The stem diameter, height plant, head diameter and yield of the sunflower increase with increasing of doses of sewage sludge. Sewage sludge increases linearly the soil organic matter and N contente in sunflowers leaf. The pH, SB, CTC(t), CTC(T), V%, H+Al, Al, and the contents of P, K, Ca, Mg, S, Zn, Cu, Mn, Fe and B in soil and leaf were not influenced by the application of sewage sludge doses up to 30 t ha-1. The results showed the importance of sewage sludge as a source of N to plants and may replace or complement the mineral fertilization of sunflower, since that it increases linearly the soil organic matter and N concentrations in sunflower leaf. The application of sewage sludge in soil may accumulate organic matter resistant to decomposition, making possible to release nutrients on the soil for longer times. The aim of this study was to evaluate growth, yield and nutrient levels in the soil and in Sunflower (Helianthus annuus L.) grown in soils containing residues of fertilizing with sewage sludge. The experiment was carried out in Red-Yellow Latosol at ICAUFMG, in Montes Claros-MG. Sunflower was cultivated in the area fertilized with sewage sludge that had been previously planted with sunflower. The treatments consisted of residual doses of sewage sludge (0; 10; 20 and 30 t ha-1, on a dry basis), in six replications, which were applied in the first cultivation of the sunflower. We evaluated the levels of nutrients in the soil and in plant, soil fertility index, stem diameter, height plant, head diameter and yield. The stem diameter, plant height, head diameter and the sunflower yield increased with the increase of sewage sludge, being the maximum values observed at dose of 30 t ha-1. The levels of organic matter and nutrients in the soil, except for calcium and magnesium, were not influenced by the residual effect of fertilization with sewage sludge. The levels of calcium and magnesium, pH, SB, CTC(t), CTC(T) and V% increased, while H+Al decreased with increasing of residual doses of sewage sludge. The leaf levels of nutrient were not influenced by the residual effects of sewage sludge treatments, except for iron and manganese, decreased with the increase of the sewage sludge residual doses. There was reduction on yield and growth characteristics of sunflower in the second cultivation, recommending new fertilization with sewage sludge every planting.